CAPAIAN KEMAMPUAN PENALARAN MATEMATIS SISWA DENGAN MODEL AIR - Nuralam Nuralam; Maulidayani Maulidayani (Jurnal Numeracy, 2020)
The mathematical concept learned in school require mathematical reasoning abilities. But the test results show the students’ mathematical reasoning ability is still relatively low. To overcome this problem, applied a learning model called Auditory Intellectually Repetition (AIR). AIR can develop mathematical reasoning abilities students through problem solving. The purpose of this study is to describe the mathematical reasoning abilty of students through the AIR learning model is higher than taught through conventional learning models.. The research design used was quasi experiment with pretest-posttest control group design. The populations in this study were all of the Eighth Grade Students of SMPN 1 Jantho and the samples taken were classes VIII-2 and VIII-1 by using the random cluster technique sampling. The data collected wasby using the mathematical reasoning ability test. The result of research through the right-hand t-test statistic test obtained 3.79 > 1.68 then accept Ha reject Ho. Therefore, it was concluded that the students’ mathematical reasoning ability learned through the AIR learning model were higher than those taught conventional learning models. Abstrak Konsep matematika dipelajari di sekolah memerlukan kemampuan penalaran matematis. Namun hasil tes menunjukkan kemampuan penalaran matematis siswa masih tergolong rendah. Salah satu alternatif membuat kemampuan penalaran matematis lebih baik melalui model pembelajaran Auditory Intelectually Repetition (AIR). Penelitian ini bertujuan mendeskripsikan kemampuan penalaran matematis siswa yang diajarkan dengan model AIR lebih baik daripada siswa yang diajarkan dengan pembelajaran konvensional. Rancangan penelitian menggunakan quasi eksperimen dengan desain pretest-posttest control grup design. Populasi dalam penelitian seluruh siswa kelas VIII SMPN 1 Kota Jantho dan sampelnya kelas VIII-2 dan VIII-1 dipilih dengan teknik cluster random sampling. Data yangdikumpulkan dengan menggunakan tes kemampuan penalaran matematis. Hasil penelitian melalui uji statistik uji-t pihak kanan diperoleh thitung > ttabel yaitu 3,79 > 1,68 maka Ha tolak Ho. Disimpulkan bahwa kemampuan penalaran matematis siswa yang diajarkan dengan model AIR lebih baik daripada yang diajarkan denganpembelajaran konvensional. Kata Kunci: Model Pembelajaran, Model Air, Kemampuan Penalaran Matematis